A Study of Human Traffic for Emergency Evacuation at Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh Residential College - Mohd Tamrin, Aminuddin; Mohd Syafiq Syazwan Mustafa, (Progress in Engineering Application and Technology, 2026)
High density residential buildings like university hostels need effective evacuation in case of emergencies to save lives. The objectives of this study is to evaluates and enhances the emergency evacuation efficiency of Block A10 of the Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh Residential College. The study simulated the emergency situation by models of occupant movement to determine the congestion points using Pathfinder program to model the building environment based on site survey and architectural plans. The simulation involved the comparison between existing evacuation routes with better approaches such as low occupancy density, route assignment according to the nearest exits and walking speed. Findings showed that the bottlenecks were narrow walkways and lack of enough exits with the width of the staircases being the main structural limitation. The best approach was to reduce occupant density (load management) to the lowest possible evacuation and the time was at 276 seconds in comparison to the current baseline of 420 seconds. These results indicate that structural constraints cannot be surmounted only through raising the velocity of movement and imply that additional signage, clearing corridors and zoning measures are all necessary to increase safety.